α1-Antitrypsin activates protein phosphatase 2A to counter lung inflammatory responses - Geraghty, Patrick; Eden, Edward; Pillai, Manju; Campos, Michael; McElvaney, Noel G; Foronjy, Robert F (American journal of respiratory and critical care medicine, 2014)
α1-Antitrypsin (A1AT) was identified as a plasma protease inhibitor; however, it is now recognized as a multifunctional protein that modulates immunity, inflammation, proteostasis, apoptosis, and cellular senescence. Like A1AT, protein phosphatase 2A (PP2A), a major serine-threonine phosphatase, regulates similar biologic processes and plays a key role in chronic obstructive pulmonary disease. Given their common effects, this study investigated whether A1AT acts via PP2A to alter tumor necrosis factor (TNF) signaling, inflammation, and proteolytic responses in this disease. PP2A activity was measured in peripheral blood neutrophils from A1AT-deficient (PiZZ) and healthy (PiMM) individuals and in alveolar macrophages from normal (60 mg/kg) and high-dose (120 mg/kg) A1AT-treated PiZZ subjects. PP2A activation was assessed in human neutrophils, airway epithelial cells, and peripheral blood monocytes treated with plasma purified A1AT protein. Similarly, lung PP2A activity was measured in mice administered intranasal A1AT. PP2A was silenced in lung epithelial cells treated with A1AT and matrix metalloproteinase and cytokine production was then measured following TNF-α stimulation. PP2A was significantly lower in neutrophils isolated from PiZZ compared with PiMM subjects. A1AT protein activated PP2A in human alveolar macrophages, monocytes, neutrophils, airway epithelial cells, and in mouse lungs. This activation required functionally active A1AT protein and protein tyrosine phosphatase 1B expression. A1AT treatment acted via PP2A to prevent p38 and IκBα phosphorylation and matrix metalloproteinase and cytokine induction in TNF-α-stimulated epithelial cells. Together, these data indicate that A1AT modulates PP2A to counter inflammatory and proteolytic responses induced by TNF signaling in the lung.